2018
DOI: 10.1523/jneurosci.3507-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Early Appearance and Spread of Fast Ripples in the Hippocampus in a Model of Cortical Traumatic Brain Injury

Abstract: Fast ripples (FRs; activity of >250 Hz) have been considered as a biomarker of epileptic activity in the hippocampus and entorhinal cortex; it is thought that they signal the focus of seizure generation. Similar high-frequency network activity has been produced by changing extracellular medium composition, by using pro-epileptic substances, or by electrical stimulation. Here we study the propagation of these events between different subregions of the male rat hippocampus in a recently introduced experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…Slice electrophysiology with a microelectrode array of 4096 channels. Slices of 350 mm were prepared as previously described (Ortiz et al, 2018). An hour after incubation of the slices in an air-liquid interface perfusing normal ACSF, the slices were transferred to a high-density CMOS (complementary metal-oxide-semiconductor) technology microelectrode array of 64 Â 64 microelectrodes (BioCam X, 3Brain) and were constantly perfused at 12 ml/min with oxygenated, standard ACSF at 34 6 0.5°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Slice electrophysiology with a microelectrode array of 4096 channels. Slices of 350 mm were prepared as previously described (Ortiz et al, 2018). An hour after incubation of the slices in an air-liquid interface perfusing normal ACSF, the slices were transferred to a high-density CMOS (complementary metal-oxide-semiconductor) technology microelectrode array of 64 Â 64 microelectrodes (BioCam X, 3Brain) and were constantly perfused at 12 ml/min with oxygenated, standard ACSF at 34 6 0.5°C.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, mefloquine was added to the acidic ACSF with the blockers and the slices were perfused over 45 min before three samples of 5 min each were acquired. A high-K 1 (20 mM) solution was perfused after completing the experiment to record high-voltage activity and check for the viability of the preparation (Ortiz et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both effects notably match what has been described in the literature 33,34 . Fast ripples 35 arise during such a beta band generating stimulus period ( Fig. S8).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that HFOs recorded using scalp EEG originate from limited cortical regions (Cuello-Oderiz et al 2017;Zelmann et al 2014). Fast ripples may be generated from regions smaller than regions that generate ripples; thus, fast ripples are less likely to be recorded on scalp EEG (Ortiz et al 2018). In the current literature, most studies on the evaluation of HFOs in epilepsy using scalp EEG have been conducted in children, with only a few conducted in adults.…”
Section: Noninvasive Hfo Recording In Epilepsymentioning
confidence: 99%